"Filling a gap: knowledge in health related science for middle school students in formal and informal contexts. Issue 2 (14th March 2020) - Azevedo, Maria Manuel; Ricardo, Elizabete; Teixeira Dos Santos, Rita; Pina-Vaz, Cidália; Rodrigues, Acácio Gonçalves
ABSTRACT: Background: Recent studies shows lack of knowledge concerning health literacy relatively microorganism/disease and the correct use of antibiotics. These facts lead to the spreading of resistant strains bacteria. Aims: The overarching goals of this study were a) to promote health literacy predominantly in respect to microorganism/disease, diseases transmission, antibiotic target and adequate antibiotic use; b) to show the importance of the transmission of health information in different environments; c) to motivate students for science research. Methods: Students' knowledge was evaluated with a survey instrument. Responses were analyzed before and after the implementation of the activity. The activity consists of an interactive lecture, slide show presentation and some practical activities. The sample includes 25 Portuguese students, 13–17 years old who attended the activity in Palácio de Cristal (Porto) and 66 students from D. Maria II School, V.N. Famalicão. Results: In this study, significant increase in knowledge about all the topics evaluated were observed both in formal and informal environments between the pre and post-test; however the best results were detected in informal contexts. Conclusion: The findings showed the importance of the implementation of scientific activities to middle-school students. This experience was valuable and helped to improve student knowledge on heath topics.